Inelastic longitudinal electron scattering C42 form factors in42Ti nucleus - Khudayer, Firas Y. (Iraqi Journal of Physics, 2019)
Inelastic longitudinal electron scattering form factors for second excited state C42 in 42Ti nucleus have been calculated using shell model theory. Fp shell model space with configuration (1f7/2 2p3/2 1f5/2 2p1/2) has been adopted in order to distribute the valence particles (protons and neutrons) outside an inert core 40Ca. Modern model space effective interactions like FPD6 and GXPF1 have been used to generate model space vectors and harmonic oscillator wave function as a single particle wave function. Discarder space (core orbits + higher orbits) has been included in (core polarization effect) as a first order correction in microscopic theory to measure the interested multipole form factors via the model space. Gogny and Michigan sum of three-range Yukawa potential (M3Y-p2) have been utilized as a residual interaction to couple the (particle-hole) pair across the model space active particles and the excitation energy of the pair is (2ħω) and four options for the used effective and residual interactions were determined for the transitions from (+0) to (+01,2,3), (+21,2,3) and (+41,2,3).